Land management and human resource development policies in Nepal - Prasad, Hari; Sigdel, Mahendra Prasad (Journal on Geoinformatics, Nepal, 2003)
Nepali life is closely dependent on land resources. Though small in size, Nepal is endowed with multiple land resources more than enough to provide good livelihood to the whole population if they are properly harnessed and utilized. Spatial diversity in terms of climate, topography and associated bio-domains is enough to illustrate Nepal's richness in resources. In order to utilize those resources, first thing for Nepal to do is to have a sustainable vision and mission based on reliable, disaggregated and organized information for harnessing of the resources towards sustainable livelihood. Such system can not be put into place in the absence of human resources capable of doing in-depth survey of lands in relation with human beings and understand inherent resources therein. Nepal has, however, not yet oriented its HRD policies towards this direction. Focus is still either on general education or engineering trades other than surveying. Whether it relates to land reform, natural resource management or agricultural development, the course of Nepal's development cannot be directed towards sustainable livelihood unless the HRD policies place due emphasis on developing quality land surveyors and land managers. This paper tries to analyse the present HRD policies of the country in the context of surveying and land management.